Hubungan Antara Status Gizi Dan Kebugaran Jasmani Dengan Keterampilan Dasar Sepakbola Siswa Putra - Nugroho, Agung Wahyu; Kusumawati, Oktaria (STKIP Al Islam Tunas Bangsa Bandar Lampung, 2019)
The purpose of this study was to determine the relationship between nutritional status and physical fitness on the basic skills of playing football in a private junior high school in the city of Bandar Lampung. This research is a correlation study. The study used a purposive sample with the limitation of male students aged 13-15 years in a private junior high school in the city of Bandar Lampung. The instrument in this study was to determine nutritional status by calculating the body mass index (BMI) or Body Mass Index by means of: (1) weight scales, (2) height measurements using a stadiometer, (3) data on height and body weight measurements if using a computer nutrisurvey program to determine the Body Mass Index (BMI). Physical fitness is measured by TKJI test with a series of tests, starting from: (1) running 50 meters in units of seconds, (2) body lifting test 60 seconds with a unit number of body lifts, (3) sitting 60 seconds in a number of sitting units , (4) upright jump in units of cm and (5) run up to 1000 meters in units of cm. The steps taken are (1) finding the average value of each variable, (2) testing the normality of data using the Kolmogorov Smirnov normality test, (3) Single correlation coefficient test with paired scores or Pearson product moment, (4) calculating degrees relationship of three variables or multiple correlation coefficients. The results showed that there was a significant relationship between nutritional status and physical fitness on the basic skills of playing football with Sig. F change 0.005 <0.05.